2017
DOI: 10.1186/s12916-017-0970-x
|View full text |Cite
|
Sign up to set email alerts
|

Choice of surrogate tissue influences neonatal EWAS findings

Abstract: BackgroundEpigenomes are tissue specific and thus the choice of surrogate tissue can play a critical role in interpreting neonatal epigenome-wide association studies (EWAS) and in their extrapolation to target tissue. To develop a better understanding of the link between tissue specificity and neonatal EWAS, and the contributions of genotype and prenatal factors, we compared genome-wide DNA methylation of cord tissue and cord blood, two of the most accessible surrogate tissues at birth.MethodsIn 295 neonates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Interindividual variation in DNA methylation was generally modest across all 9 isolated cell types from CB and CT, with more variation among CT cell types (median IQR: Endothelial 1.7%, Stromal 1.7%, Epithelial 2.1%) than CB cell types (median IQR ranged from 1.1% to 1.2%). Consistent with our earlier finding [17], we found greater interindividual variation across whole CT samples (median IQR: 2.0%, 2.2% for USCS and frozen CT) than CB (median IQR: 1.4% and 1.6% for unsorted leukocytes and buffy coat).
10.1080/15592294.2018.1522929-F0005Figure 5.Comparison of interindividual variation in unfractionated cord tissue (CT), cord blood (CB), and their constituent cell types: CT showed more variable CpGs than CB. (a) Distribution of DNA methylation inter-quartile ranges (IQR) in each cell type/tissue.
…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Interindividual variation in DNA methylation was generally modest across all 9 isolated cell types from CB and CT, with more variation among CT cell types (median IQR: Endothelial 1.7%, Stromal 1.7%, Epithelial 2.1%) than CB cell types (median IQR ranged from 1.1% to 1.2%). Consistent with our earlier finding [17], we found greater interindividual variation across whole CT samples (median IQR: 2.0%, 2.2% for USCS and frozen CT) than CB (median IQR: 1.4% and 1.6% for unsorted leukocytes and buffy coat).
10.1080/15592294.2018.1522929-F0005Figure 5.Comparison of interindividual variation in unfractionated cord tissue (CT), cord blood (CB), and their constituent cell types: CT showed more variable CpGs than CB. (a) Distribution of DNA methylation inter-quartile ranges (IQR) in each cell type/tissue.
…”
Section: Resultssupporting
confidence: 94%
“…As we quantified interindividual variation in a small sample size (n = 10), we expect the overall proportion of useful CpGs to increase with increasing sample size, with a retained trend for CT to still have a higher proportion of variable CpGs than CB. We have also previously reported this observation from a comparison of whole CT and CB DNA methylation profiles from a larger cohort drawn from the same population [17]. …”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…This project showed that tissues could be clustered according to their germinal origin: ectodermal, such as brain and skin, endodermal, such as lung and gastrointestinal, and mesodermal, such as blood and muscle . Cord blood was clustered with hematopoietic stem cell tissues and cord tissue was clustered with mesenchymal stem cell tissues . Saliva is a mixture of cells, mainly buccal cells and leucocytes, and has been shown to be a fairly representative surrogate tissue for the brain .…”
Section: Epigenetics Vary Between Tissuesmentioning
confidence: 99%